(untitled) (Tempo e Argumento, 2025)
This article discusses the writings of prisoners and their importance for understanding the dynamics of social relations in prisons, as well as the subjective dimension of inmates. It particularly analyzes the contribution of a posthumous work by Abdias Nascimento to the knowledge of the functioning of the State Penitentiary in São Paulo, where he was imprisoned from 1943 to 1944. Abdias Nascimento, in addition to narrating his experiences and feelings as an inmate, subjected to the rigors of discipline and punishments, sought to give voice to several prisoners so they could tell their stories of crime and their lives in the Penitentiary. Abdias Nascimento lived through a period of reform of the Penitentiary, undertaken by the physician Flamínio Fávero, who sought to reverse the rigors of silence and the many punishments that had been imposed until then, as well as to create new routines, by allowing greater participation of prisoners in the structuring of the daily life of that prison. These reforms allowed the emergence of the Theater of the Sentenced, under the direction of Abdias himself. His writing, therefore, constitutes a document that records the daily practices of that prison, the disciplinary mechanisms imposed, and prisoners’ feelings. It also preserves a page in the history of prisons in Brazil.